Influence of qualitative composition of raw materials on the production of hydrogen by microorganisms - Голуб, Н. Б.; Жураховська, Д. І.; Чумак, В. Л. (Proceedings of National Aviation University (archive), 2013)
The aim was to study the influence of the quality of the agricultural waste materials to the process of producing hydrogen group of microorganisms. Researches were conducted by microbiological and chromatographic methods of analysis. The process of producing hydrogen passes using agricultural waste in anaerobic mesophilic regime for the use of groups of microorganisms. On all types of waste found production of hydrogen. The pretreatment of raw material increases access of microorganisms to nutrients, destruction of lignino-cellulosic frame and decontamination of methanegenic bacterias. The aging of culture leads to transition the butyric type of fermentation to acetone-butyric type, which causes decreasing the yield of hydrogen. The maximum yield of hydrogen was 128 g H2 per kg of cellulose. It was obtained by using barley straw as raw material, which contains great amount of hemicelluloses.